The Intellectual and Religious Dimensions of the Islamic Persian Literary Culture in India During the Thirteenth Century - Siddiqui, Iqtidar Husain (Intellectual Discourse, 2013)
The foundation of an independent Muslim sultanate in north India in the beginning of the thirteenth century attracted, apart from soldiers, ʿulamā' and men of sciences and arts to India. Every town and city was studded with institutions of learning (Madrasas) for catering to the intellectual, religious and cultural needs of Muslims. Since the immigrants came mainly from Persian speaking lands of Khurasan and Central Asia and, with the exception of ʿulamā, they could not benefit from Islamic literature in Arabic directly, the important works on Islam i. e., books on religion, ethics, philosophy and history were translated into Persian for the benefit of the Persian-speaking intelligentsia. The munificent patronage extended by the ruling elite to scholars also encouraged them to produce original works in various sciences. Efforts made by the rulers and scholars in this respect led to the efflorescence of learning and culture during the subsequent period. This study presents an analysis of the intellectual dimension of this early Indo-Persian literary culture in Islamic perspective and to show how much the Muslims were ahead of others in formulating ideas of political economy and social welfare.